2020
DOI: 10.13057/biodiv/d211215
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of yield and pest and disease resistance of cocoa clones in Kolaka District, Southeast Sulawesi, Indonesia

Abstract: Abstract. Rubiyo, Dewi YA, Imran, Salim A, Baharudin, Indrawanto C, Ratule MT. 2020. Evaluation of yield and pest and disease resistance of cocoa clones in Kolaka District, Southeast Sulawesi, Indonesia. Biodiversitas 21: 5698-5607. Cocoa is one of the main plantation commodities in Indonesia. It is an important source of foreign exchange and employment. Currently, Indonesian cocoa production and productivity, including in Southeast Sulawesi, are declining due to pests and diseases. In addition, there is a lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
1
0
3
Order By: Relevance
“…Frequent harvest aimed to remove the infested cocoa pods by CPB and PSB by burying the them into the soil [13]. Observations in Guguak showed that the damage level of CPB was the lowest compared with other districts.…”
Section: Discussionmentioning
confidence: 99%
“…Frequent harvest aimed to remove the infested cocoa pods by CPB and PSB by burying the them into the soil [13]. Observations in Guguak showed that the damage level of CPB was the lowest compared with other districts.…”
Section: Discussionmentioning
confidence: 99%
“…Hal tersebut dikarenakan tanaman ini dapat berbunga dan berbuah sepanjang tahun, sehingga dapat menjadi sumber pendapatan harian atau mingguan bagi masyarakat (Hafifah, 2018). Selain itu, kakao atau coklat sendiri telah dikenal sebagai komoditi penting di dunia dan merupakan komoditi unggulan dalam program pengembangan di sektor pertanian (Rubiyo & Siswanto, 2012). Luas areal tanam di Kabupaten Lombok Utara sekitar 3000 Ha, akan tetapi produktivitas dan profitabilitas usaha tani pada komoditi ini sangat rendah karena terdapat beberapa kendala yang berkaitan dengan aspek teknis usaha tani (Salako et al, 2018).…”
Section: Abstrakunclassified
“…Keterjadian serangan hama dan penyakit diamati secara visual, dan dihitung persentase buah terserang, dengan kategori ringan (<20%), sedang (20-50%), berat (>50%) (Rubiyo et al, 2020). Untuk pengamatan keterjadian penggerek buah kakao, maka buah dipecah dan diamati kerusakan dan perlekatan biji.…”
Section: Jurnal Pengabdian Fakultas Pertanian Universitas Lampungunclassified